A case report of an asymptomatic necrotic Meckel's diverticulum in an inguinal hernia during elective surgery in a resource limited setting: Littre's hernia. (April 2023) - Odongo, Charles Newton; Godier-Furnemont, Amandine; Moro, Joshua; Oyania, Felix
Abstract: Introduction and importance: Although the common complications of Meckel's diverticulum (MD) are well known, that these congenital intestinal outpouchings may become involved as the content of abdominal hernia sacs is not well appreciated. MD is the most prevalent congenital abnormality of the gastrointestinal tract, but involvement in a hernia, known as Littre's hernia (LH), accounts for less than 1 % of MD cases. Incarcerated LH has been reported sporadically in the literature, with MD found in the sacs of paraumbilical, femoral, inguinal, and incisional hernias. Presentation of case: We report a LH in a 3-year-old male child who was scheduled for elective herniotomy for a reducible left inguinal hernia. Intraoperatively we found the hernia sac contained a necrotic and perforated MD with viable associated bowel loop. The patient was successfully managed by diverticulectomy and primary repair through a trans-inguinal incision and herniotomy was performed. Clinical discussion: LH is a rare presentation of MD, and preoperative diagnosis of LH is challenging. Even in the case of a strangulated MD, a patient may not present with the typical signs and symptoms associated with compromised viscous. Once identified, repair of Littre hernia consists of resection of the diverticulum, or segmental bowel resection if necessary, and herniotomy. Conclusion: The finding of a perforated MD during elective hernia repair emphasizes the importance of awareness of unusual variants of inguinal hernia, and the necessity of identifying a MD given the risk of sequelae in the case of necrosis or perforation, if not repaired. Highlights: Littre's hernia is a rare presentation of Meckel's diverticulum. Strangulated Meckel's diverticulum may not present with typical symptoms of compromised viscous. Identification of perforated Meckel's diverticulum is crucial, given risk associated if missed and unrepaired.